PENGARUH FREE CASH FLOW DAN PROFITABILITAS TERHADAP EARNING MANAGEMENT DAN NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Property, Real Estate dan Building construction Di BEI Tahun 2012-2016) - Pelsa Windra; Haryetti Haryetti; Ahmad Fauzan Fathoni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
The value of firm is very important,ifthe value of firm increase, shareholder's prosperity will also increase.Based on the phenomenon of data, the value of firm in the property, real estate and building construction in Indonesian stock exchangeoccurred sharp fluctuations from the year 2012-2016. The aims of this study is to determine the direct and indirect effect of free cash flow and profitabilityto earning management and the value of firm.Non random sampling technique, that is purposive sampling method used to get the sample of this study. The analytical method used is path analysis with the help of LISREL program. The results show thatfree cash flow has a negative but not significant influence on the value of firm. Profitability has a positive and significant influence on the value of firm. Free cash flow and profitability have positive and significant effect on earning management. Earning management has a negative and significant influence on the value of firm. Free cash flow and profitabilityhave negative and significant influence on the value of the company through earning management.Keyword : Free cash flow, profitability, earning management, value of firm